1995
DOI: 10.1149/1.2048519
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Ether and Carbonyl Oxygens to Lithium Ion

Abstract: The power of a lithium battery depends on the mobility of the lithium ion. Since the lithium ion, Li § binds to the mobile and nonmobile molecules in the electrolyte, then the strength of the Li § binding affects the conductivity of the electrolyte. The binding of dimethyt ether, diethyl ether, acetone," ethylene carbonate, and propylene carbonate to lithium ion is calculated using ab initio quantum mechanics techniques. The binding of water and acetaldehyde to Li + has been calculated for higher coordination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
62
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 3 publications
12
62
2
Order By: Relevance
“…This type of isotope effect may exist in process (i). Lithium ions are selectively coordinated by EC molecules in the EC/MEC mixed solution and the solvation number of the lithium ion is four in the primary solvation sphere [16,17]. The separation factor, S dif , expected for the diffusion process of Li + (EC) 4 in the electrolyte is then estimated to be 1.0014, much smaller than the S values observed in this work.…”
Section: Lithium Isotope Effectscontrasting
confidence: 59%
See 1 more Smart Citation
“…This type of isotope effect may exist in process (i). Lithium ions are selectively coordinated by EC molecules in the EC/MEC mixed solution and the solvation number of the lithium ion is four in the primary solvation sphere [16,17]. The separation factor, S dif , expected for the diffusion process of Li + (EC) 4 in the electrolyte is then estimated to be 1.0014, much smaller than the S values observed in this work.…”
Section: Lithium Isotope Effectscontrasting
confidence: 59%
“…The integrated quantity of electricity was varied from 6.1 to 54.5 C, and the chemical formula of the formed Li-GICs calculated from the integrated quantities of electricity and the amount of graphite flakes loaded on the copper foils was from Li 0.029 C to Li 0. 16 C. An example of the changes of the cathode potential and the electric current during an electrolytic course (Run LC2-3) is shown in Figure 3. The cathode potential swiftly decreased at the very beginning of the electrolysis, reached the predetermined value (0.02 V in this case) and was kept constant thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…A combined photoelectron spectroscopy and ab initio investigation of the complexes of HF with dimethyl ether and dimethyl sulÐde have been carried out by Carnovale et al 25 LiF complexes of ammonia and water have been investigated theoretically by few authors26h31 and Ault and Pimental32 have provided structures of and H 3 NÉ É ÉLiCl by studying the vibrations of these complexes H 3 NÉ É ÉLiBr isolated in inert matrices. Li`affinity of dimethyl ether has been reported by Abboud et al, 33 Blint,34 and also by Smith et al 35 Woodin and Beauchamp36 have studied the Li`affinity of trimethylamine and dimethyl ether. We present here an ab initio and DFT computational study of LiF/HF complexes with the above lone pair donors, and compare our results with the available experimental values.…”
Section: Introductionmentioning
confidence: 81%
“…EC, with high polarity and dielectric constant, is one of the most important ingredients in the electrolyte. In 1995, Blint 58 calculated the binding energy of Li + with EC and showed that it is higher than water and several other ether and carbonyl oxygen containing species. In 2000, Li and Balbuena 14 first applied QC to investigate the experimentally proposed EC reduction mechanism proposed by Aurbach et al 59 This is a significant step, as the majority of SEI reaction mechanisms in the literature were deduced from experimentally observed products, and QC can confirm these mechanisms by calculating the energies of the intermediate structures along the proposed reaction pathways.…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%